1999
DOI: 10.1530/eje.0.1410279
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-producing adenoma without hypertension: a report of two cases

Abstract: Normotensive primary hyperaldosteronism is exceedingly rare. We report two new cases of this syndrome in two middle-aged women, one of Asian origin. The presenting signs were tetany in one case and an adrenal mass in the other. Neither patient had hypertension, despite repeated measurements with a manual armlet. A typical biological profile of primary hyperaldosteronism was demonstrated in both patients, including hypokalemia with inappropriate kaliuresis, elevated resting plasma aldosterone, and undetectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
(45 reference statements)
0
23
0
2
Order By: Relevance
“…However, clinical and biochemical features vary widely, and normotensive PA patients have been described. 1,9 The aim of this study was to evaluate the prevalence of PA and to relate this to a clinical profile of hypertensive disease. We considered hypertension severity, age at onset, and quantity of drugs necessary for blood pressure control.…”
mentioning
confidence: 99%
“…However, clinical and biochemical features vary widely, and normotensive PA patients have been described. 1,9 The aim of this study was to evaluate the prevalence of PA and to relate this to a clinical profile of hypertensive disease. We considered hypertension severity, age at onset, and quantity of drugs necessary for blood pressure control.…”
mentioning
confidence: 99%
“…Several possible causes of the nonhypertensive form of primary aldosteronism must be considered. Vantyghem et al 8 reported that blood pressure fell markedly after aldosterone-producing adenoma surgery in their nonhypertensive patients, suggesting that hyperaldosteronism had induced relative hypertension; however, the blood pressure remained at nonhypertensive levels due to very low spontaneous baseline levels. Another major explanation is that some of the study participants had mild, subclinical hyperaldosteronism because they were in the early phase of this disease, and hypertension may develop later and be detected on follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…However, the clinical and biochemical features vary widely. Sporadic cases of normotensive primary aldosteronism have been rarely described, [6][7][8][9] and normotensive patients have been observed among individuals with familial hyperaldosteronism type-I (FH-I); 10 however, the prevalence of this disease in normotensive and mild hypertensive populations has not been determined. 6,7,11,12 The purpose of this study was to examine the prevalence of primary aldosteronism in an unselected Japanese population with prehypertension and stage 1 hypertension at a health screening center.…”
Section: Introductionmentioning
confidence: 99%
“…Recent statistical data have demonstrated that more than one half of patients with PA were normokalemia (1). Although the hypertension is usually mild and may fluctuate, only 27 cases with consistently normotensive, due to APA or IHA, have been reported so far (25)(26)(27). The mechanism(s) underlying the maintenance of normal BP levels, despite an overproduction of aldosterone, are unknown.…”
Section: Discussionmentioning
confidence: 99%